PERAN PANTI ASUHAN ALMUHAJIRIN KOTA PALU DALAM MEMBENTUK KARAKTER RELIGIUS ANAK DITINJAU DARI HUKUM ISLAM - Cikka, Hairuddin; Hamid, Usman (Musawa: Journal for Gender Studies, 2020)
This research focuses on the role of Al Muhajirin Orphanage in Palu City in building religious character of children reviewed from Islamic law. This research used qualitative research method through observation, in-depth interviews, and documentation study. The data obtained were analyzed using data reduction technique, data presentation, data verification, and drawing conclusions. The results showed that: (1). The caregivers' efforts in building the religious character of children were strongly supported by the situation and condition of Al Muhajirin Orphanage marked by the stay of foster children in the dormitory, so that religious-based character building could be performed optimally. The religious-based character values that were developed including being religious, disciplined, like to read, caring for the environment, responsible, and honest. The implementation of religious-based character formation aims to make a person as a good human being. The forms of implementation of character education are manifested by cultivating the faith, providing guidance, providing good role models, enforcing rules, providing advice, motivation, and conducting supervision (2). Islamic law review of the role of caregiver included educating, teaching, and training. Educating means transmitting and developing the values of life/personality. Teaching means transmitting and developing science and technology. While, training means developing skills in foster children based on QS. Al-Kahfi [18] 66-70. Meanwhile, character building in Islam is the same as moral education and it is also a purification of the soul and character of humans to become righteous humans based on the Quran and hadith.